Worker Club in the System of Proletarian Worship Cultural-Enlightening Organizations - Oksana Kravchenko (Pedagogical Discourse, 2013)
Worker club as a Proletarian worship structural item is regarded in the article. The main objects, tasks and activity directions in the context of cultural-enlightening movement are defined.